Quantification of ADAMTS-1 Levels in Generalized Periodontitis Patients: Impact of Non-Surgical Periodontal Therapy - Girish Suragimath (International Journal of Medical Toxicology and Legal Medicine, 2024)
Generalized periodontitis is a prevalent inflammatory disease affecting the supporting structures of the teeth, leading to progressive tissue destruction. This study aimed to quantify ADAMTS-1 levels in patients with generalized periodontitis and evaluate the impact of non-surgical periodontal therapy (NSPT) on these levels. The study included 60 participants: 40 with generalized periodontitis and 20 healthy controls. Gingival crevicular fluid (GCF) samples were collected at baseline and 1, 3, and 6 months post-NSPT for analysis using enzyme-linked immunosorbent assay (ELISA). Baseline ADAMTS-1 levels were significantly higher in periodontitis patients compared to controls (p < 0.01). Following NSPT, ADAMTS-1 levels significantly decreased at all follow-up points (p < 0.01), correlating with improvements in clinical parameters such as probing depth, clinical attachment level, bleeding on probing, and plaque index. The findings suggest that ADAMTS-1 is a potential biomarker for periodontal disease and treatment efficacy, providing insights into the molecular changes associated with NSPT and contributing to the development of targeted periodontal therapies.